PENGENDALIAN INFLASI, MONETER, DAN FISKAL DALAM PERSPEKTIF EKONOMI MAKRO ISLAM - Triwahyuni Triwahyuni (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
The economic development of a country, including in Indonesia, cannot be separated from the monetary and fiscal policies adopted by each country concerned. However, the monetary and fiscal policies adopted by each country vary depending on the real economic conditions, the direction and development objectives to be achieved. In principle, the management of monetary and fiscal policies aims to maintain the inflation rate by regulating the circulation of money and interest rates which tend to increase in society. The purpose of this research is to find out how the government controls inflation, monetary and fiscal, and their impact on the economy from an Islamic macroeconomic perspective. The method used is library research method and the data used is secondary data which is in accordance with a number of relevant literature. As an effort to overcome inflation, monetary and fiscal policies, the government needs to carry out macroeconomic policies in relation to achieving the inflation target and economic growth. Thus, every country needs to maintain economic stability in accordance with the challenges it faces.